A method for preparing a foamed nickel

CN118326187BActive Publication Date: 2026-10-27FIRST SEMICON MATERIALS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410498143.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-24
Publication Date
2026-10-27
Estimated Expiration
2044-04-24

AI Technical Summary

Technical Problem

但该方案最高只能制备得到孔隙率为52.4%的多孔镍

Benefits of technology

[0018]本发明提供了一种泡沫镍的制备方法。本发明使用镍单质粉作为原料,氧化锌作为造孔剂,马铃薯淀粉作为粘结剂,由于氧化锌熔点为1975℃,高于烧结温度,在烧结时不会熔化,将镍粉与氧化锌粉混合均匀,再通过冷压、低温热压、烧结的方法制成烧结胚,制作成胚体后,利用镍与碱不反应而氧化锌与碱反应的特点,将氧化锌与碱反应除去氧化锌而留下大小均匀的孔径,且孔径大小由氧化锌颗粒大小而决定。本发明关键在于以冷压和低温热压后烧结的方式结合马铃薯粉粘结剂,才得以制备得到孔隙率为80~86%的高孔隙率泡沫镍。本发明利用烧结溶解法制备超高孔隙率泡沫镍,方法简单易操作,对于批量化生产具有重要意义。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the field of powder metallurgy, in particular to a preparation method of foamed nickel, which comprises the following steps: mixing nickel element, zinc oxide and potato starch, and sequentially performing cold pressing, low-temperature hot pressing and sintering; the pressure of the low-temperature hot pressing is 80-100 MPa, the temperature is 150-200 DEG C, and the time is 3-5 h; the obtained product is soaked in lye to obtain foamed nickel. The application is characterized in that the sintering mode after cold pressing and low-temperature hot pressing is combined with the potato powder binder to prepare the foamed nickel with a porosity of 80-86%. The foamed nickel is prepared by using the sintering dissolution method, the method is simple and easy to operate, the high-temperature dissolution mode is used during dissolution to ensure that the obtained foamed nickel is open-pored, and the foamed nickel is better than the semi-open semi-closed hole foamed nickel prepared by using the traditional sintering dissolution method or the gasification pore forming method. Experiments show that the porosity of the foamed nickel prepared by using the preparation method reaches 86% at most.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of powder metallurgy, specifically a method for preparing nickel foam. Background Technology

[0002] Foamed metals are metallic materials with a microporous structure. Their lightweight, high strength, and excellent thermal and sound insulation properties make them promising for various applications. Their unique structure and properties have made them a research hotspot in lightweight materials, with broad application prospects in aerospace, automotive manufacturing, and construction. Traditional foamed metal materials mainly include aluminum foam and magnesium foam, which have a long history of development and relatively mature processing technologies in the field of lightweight materials. However, traditional foamed metal materials still have certain limitations in terms of strength, plasticity, and wear resistance, and cannot meet the needs of some other fields.

[0003] In recent years, new types of foamed metal materials have emerged, including foamed nickel. Research on electroplating methods for foamed nickel is extensive, while reports on other methods are scarce. The main preparation steps of the electroplating method include raw material preparation, conductivity treatment, electroplating, calcination, reduction, and annealing. Electroplating has advantages such as high technological maturity, convenient operation, and simple equipment. Foamed nickel produced by this method exhibits good pore uniformity and excellent corrosion resistance. However, it is costly, involves complex processes, generates significant wastewater, and is environmentally unfriendly.

[0004] In their paper "Preparation of Porous Nickel and Its Structural Properties by Powder Sintering and Dissolution Method," Wang Tianyao et al. used nickel powder as raw material and K2CO3 as a pore-forming agent. The powders were weighed and mixed in a specific ratio, and the uniformly mixed powder was placed in a mold for axial pressing. After pressing, the sample was dried and then sintered in an atmosphere resistance furnace. Argon gas was introduced during sintering, and the sintering temperature was 1000–1200℃ for 1–3 hours. After sintering, the sample was dissolved in water to remove residual pore-forming agent. After the pore-forming agent dissolved, it was dried in a drying oven to obtain a porous nickel sample. However, this method could only prepare porous nickel with a maximum porosity of 52.4%. Summary of the Invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a method for preparing nickel foam, which can prepare ultra-high porosity nickel foam with a porosity of close to 90%.

[0006] This invention provides a method for preparing nickel foam, comprising the following steps:

[0007] S1) Nickel, zinc oxide and potato starch are mixed and then subjected to cold pressing, low-temperature hot pressing and sintering in sequence; the low-temperature hot pressing is performed at a pressure of 80~100 MPa, a temperature of 150~200℃ and a time of 3~5 h.

[0008] S2) The product obtained in step S1) is soaked in an alkaline solution to obtain nickel foam.

[0009] The inventors of this application have creatively discovered that in the process of preparing nickel foam using the pore-forming method, the use of cold pressing and low-temperature hot pressing followed by sintering allows potato starch to exert its binding effect. This improves the density of the preform and results in nickel foam with extremely high porosity. Furthermore, this method has lower equipment requirements, lower power consumption, and lower cost, overcoming the problems of high pressure and demanding equipment required by traditional cold pressing methods. It also overcomes the issue that using other traditional binders with low-temperature hot pressing followed by sintering cannot achieve high porosity or even produce nickel foam at all. The porosity of the nickel foam described in this invention is 80-86%.

[0010] This invention utilizes zinc oxide as a pore-forming agent. Zinc oxide has a high melting point and good alkali solubility, preventing nickel powder from melting before a framework is formed, thus improving pore size uniformity and increasing porosity and yield. The zinc oxide used in this invention is spherical zinc oxide with a particle size of 0.3~0.6mm. This invention uses potato starch as a binder, which improves the adhesion between nickel powders during low-temperature hot pressing, increasing their mechanical strength. It is also environmentally friendly and low-cost. The potato starch used in this invention has a particle size of 70~90 μm. The elemental nickel used in this invention is nickel powder with an average particle size of 10~20 μm. The mass ratio of elemental nickel, zinc oxide, and potato starch in this invention is 1:(8~9):(0.15~0.6), preferably 1:(8~9):0.15. In one embodiment, the mass ratio of elemental nickel, zinc oxide, and potato starch is 1:8:0.15 or 1:9:0.15.

[0011] This invention first involves mixing elemental nickel, zinc oxide, and potato starch. Specifically, this mixing is performed under a protective gas atmosphere through three-dimensional homogenization. In some embodiments of this invention, the elemental nickel, zinc oxide, and potato starch are placed in a mixing container, and after being filled with a protective gas for 20-30 minutes, the mixture is homogenized in a three-dimensional manner at a rotation speed of 8-12 r / min for 20-26 hours. The protective gas used in this invention is selected from at least one of nitrogen, helium, neon, or argon.

[0012] This invention involves mixing elemental nickel, zinc oxide, and potato starch, followed by sequential cold pressing, low-temperature hot pressing, and sintering. Specifically, under a protective gas atmosphere, the mixed material is sequentially cold-pressed and then low-temperature hot-pressed, followed by depressurization and sintering. In some embodiments of this invention, the mixed material is cold-pressed under a protective gas atmosphere; then heated to the temperature required for low-temperature hot pressing at a rate of 15-25°C / min, preferably 20°C / min, and then pressurized to the pressure required for low-temperature hot pressing; then depressurized and heated to the temperature required for sintering; and finally cooled to room temperature under a protective gas atmosphere after the temperature drops to 600°C. The cold pressing pressure of this invention is 40-60 MPa, and the time is 5-10 min; the cold pressing is performed at room temperature, for example, between 20-35°C; in one embodiment of this invention, the cold pressing is performed at 25°C. The low-temperature hot pressing described in this invention is performed at a pressure of 80-100 MPa, a temperature of 150-200°C, and a time of 3-5 hours; the sintering temperature is 1000-1200°C, and the time is 2-3 hours. The protective gas described in this invention is the same as described above and will not be repeated.

[0013] This invention involves loading the mixed materials into a mold, and then placing the mold containing the mixed materials into a vacuum hot press furnace for sequential cold pressing, low-temperature hot pressing, and sintering. The process of loading the mixed materials into the mold is as follows: two pieces of graphite paper, the same size as the bottom of the mold, are placed at the bottom of the mold; the mixed powder is then slowly spread evenly in the graphite mold; and two more pieces of graphite paper, the same size as the bottom of the mold, are placed on top of the powder. In some embodiments of this invention, the mold is selected from graphite molds or stainless steel molds; the shape and size of the mold can be determined according to requirements.

[0014] This invention involves sequentially subjecting the mixed materials to cold pressing, low-temperature hot pressing, and sintering. Before immersing the sintered material in an alkaline solution, the invention also includes a polishing and cleaning process. Specifically, the sintered material is mixed with a polishing agent and polished using a metallographic polishing machine until no graphite paper is visible under a microscope.

[0015] This invention involves polishing and cleaning the sintered material, followed by immersion in an alkaline solution at 200-250°C for 2-4 hours. In some embodiments, the alkaline solution is slowly poured into a high-temperature, high-pressure reactor, and then the sintered material is slowly added. The alkaline solution is selected from at least one of sodium hydroxide solution, potassium hydroxide solution, and barium hydroxide solution. The concentration of the alkaline solution is 230-250 g / L. In some embodiments, the alkaline solution is selected from a sodium hydroxide solution with a concentration of 230-250 g / L. This invention uses a high-temperature, high-pressure reactor for high-temperature dissolution during pore-forming, ensuring that the resulting nickel foam is open-cell, which is superior to the semi-open / semi-closed pore nickel foam obtained by traditional sintering-dissolution or vaporization pore-forming methods.

[0016] The present invention involves soaking the sintered material in an alkaline solution, then washing the material obtained after soaking in the alkaline solution in boiling water for 2-4 hours; specifically, the material obtained after soaking in the alkaline solution is placed in a conventional reaction vessel containing pure water, and the reaction vessel containing the preform and its pure water is boiled for 2-4 hours for washing, then the material is taken out and rinsed with running water 3-5 times, and then dried at 80°C for 8-10 hours.

[0017] The porosity of the foamed nickel can be calculated by weight. Specifically, the weight of the material after the polishing and cleaning treatment and before the alkali soaking is denoted as m1, and the weight of the material after drying is denoted as m2. The porosity calculation formula is (m1-m2)×100% / m1.

[0018] This invention provides a method for preparing nickel foam. The method uses elemental nickel powder as a raw material, zinc oxide as a pore-forming agent, and potato starch as a binder. Since zinc oxide has a melting point of 1975℃, which is higher than the sintering temperature, it will not melt during sintering. The nickel powder and zinc oxide powder are mixed evenly, and then a sintered preform is formed through cold pressing, low-temperature hot pressing, and sintering. After forming the preform, taking advantage of the characteristic that nickel does not react with alkali while zinc oxide does, the zinc oxide is removed by reacting with the alkali, leaving uniformly sized pores. The pore size is determined by the size of the zinc oxide particles. The key to this invention lies in combining cold pressing and low-temperature hot pressing with sintering, along with potato starch as a binder, to obtain high-porosity nickel foam with a porosity of 80-86%. This invention utilizes a sintering-dissolution method to prepare ultra-high porosity nickel foam; the method is simple and easy to operate, and is of great significance for mass production. Detailed Implementation

[0019] This invention discloses a method for preparing nickel foam. Those skilled in the art can refer to this document and appropriately modify the process parameters to achieve the desired result. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention. The method and application of this invention have been described through preferred embodiments, and those skilled in the art can clearly modify or appropriately change and combine the method and application described herein without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.

[0020] The present invention will be further described below with reference to the embodiments: Example 1

[0021] Prepare nickel powder with a purity of 99.99% and an average particle size of 10-20 μm; analytically pure spherical zinc oxide with a particle size of 0.5 mm; and potato starch with a particle size of 80 μm, weighing 500 g, 4000 g, and 75 g respectively. All are poured into a 2 L stainless steel container, and argon gas is introduced for 20 min. The mixture is then homogenized in a three-dimensional powder mixer at 8 r / min for 20 h. After homogenization, the powder is removed and placed in a 90 mm diameter circular graphite mold. Two 90 mm diameter circular graphite papers are placed at the bottom, and the homogenized powder is slowly spread evenly in the mold. Two more 90 mm diameter circular graphite papers are placed on top. Under argon gas purging, the mixture is cold-pressed at 40 MPa for 5 min; then heated to 150 °C at a rate of 20 °C / min, and then pressurized to 80 MPa for 3 h. Afterward, the pressure is released, and the mixture is heated to 1000 °C without pressure and held at that temperature for 2 hours. h; After the temperature drops to 600℃, it is cooled to room temperature by filling with inert gas. After removal, it is polished using a metallographic polishing machine to remove the graphite paper on the surface of the hot-pressed blank. During polishing, metallographic spray polishing agent is sprayed 5 times. After polishing, its weight m1 is weighed, which is 4532 g. The polished blank is placed in a high-temperature and high-pressure reactor containing 2 L of 230 g / L sodium hydroxide solution, heated to 200℃, and kept at this temperature for 2 h to dissolve. Then, the blank is transferred to a reactor containing 2 L of fresh pure water and boiled for 2 h. After removing the blank, it is rinsed 3 times with running water and then vacuum dried at 80℃ for 8 h to obtain dry nickel foam, which weighs 676 g and is recorded as m2. The porosity is calculated to be 85.1%. Example 2

[0022] Prepare nickel powder with a purity of 99.99% and an average particle size of 10-20 μm; analytically pure spherical zinc oxide with a particle size of 0.5 mm; and potato starch with a particle size of 80 μm, weighing 500 g, 4000 g, and 75 g respectively. All are poured into a 2 L stainless steel container, and argon gas is introduced for 25 min. The mixture is then homogenized in a three-dimensional powder mixer at 10 r / min for 24 h. After homogenization, the powder is removed and placed in a 90 mm diameter circular graphite mold. Two 90 mm diameter circular graphite papers are placed at the bottom, and the homogenized powder is slowly spread evenly in the mold. Two more 90 mm diameter circular graphite papers are placed on top. Under argon gas purging, the mixture is cold-pressed at 50 MPa for 8 min; then heated to 170 °C at a rate of 20 °C / min, and pressurized to 90 MPa for 4 h; finally, the pressure is released, and the mixture is heated to 1100 °C without pressure and held at that temperature for 3 hours. h; After the temperature drops to 600℃, it is cooled to room temperature by filling with inert gas. After removal, it is polished using a metallographic polishing machine to remove the graphite paper on the surface of the hot-pressed blank. During polishing, metallographic spray polishing agent is sprayed 5 times. After polishing, its weight m1 is weighed, which is 4528 g. The polished blank is placed in a high-temperature and high-pressure reactor containing 2 L of 240 g / L sodium hydroxide solution, heated to 230℃, and kept at this temperature for 3 h to dissolve. Then, the blank is transferred to a reactor containing 2 L of fresh pure water and boiled for 3 h. After removing the blank, it is rinsed with running water 4 times and then vacuum dried at 80℃ for 8 h to obtain dry nickel foam, which weighs 632 g and is recorded as m2. The porosity is calculated to be 86%. Example 3

[0023] Prepare nickel powder with a purity of 99.99% and an average particle size of 10-20 μm; analytically pure spherical zinc oxide with a particle size of 0.5 mm; and potato starch with a particle size of 80 μm, weighing 500 g, 4500 g, and 75 g respectively. All are poured into a 2 L stainless steel container, and argon gas is introduced for 30 min. The mixture is then homogenized in a three-dimensional powder mixer at 12 r / min for 26 h. After homogenization, the powder is removed and placed in a 90 mm diameter circular graphite mold. Two 90 mm diameter circular graphite papers are placed at the bottom, and the homogenized powder is slowly spread evenly in the mold. Two more 90 mm diameter circular graphite papers are placed on top. Under argon gas purging, the mixture is cold-pressed at 60 MPa for 10 min. The temperature is then increased to 200℃ at a rate of 20℃ / min, and the pressure is increased to 100 MPa for hot pressing for 5 h. Afterward, the pressure is released, and the mixture is heated to 1200℃ without pressure and held at that temperature for 4 hours. h; After the temperature drops to 600℃, it is cooled to room temperature by filling with inert gas. After removal, it is polished using a metallographic polishing machine to remove the graphite paper on the surface of the hot-pressed blank. During polishing, metallographic spray polishing agent is sprayed 5 times. After polishing, its weight m1 is weighed, which is 4542 g. The polished blank is placed in a high-temperature and high-pressure reactor containing 2 L of 250 g / L sodium hydroxide solution, heated to 250℃, and kept at this temperature for 4 h to dissolve. Then, the blank is transferred to a reactor containing 2 L of fresh pure water and boiled for 4 h. After removing the blank, it is rinsed 5 times with running water and then vacuum dried at 80℃ for 10 h to obtain dry nickel foam, which weighs 647 g and is recorded as m2. The porosity is calculated to be 85.8%. Comparative Example 1

[0024] Prepare nickel powder with a purity of 99.99% and an average particle size of 10-20 μm; analytical grade spherical zinc oxide with a particle size of 0.5 mm; and polyethylene with a particle size of 80 μm, weighing 500 g, 4500 g, and 75 g respectively. All are poured into a 2 L stainless steel container, and argon gas is introduced for 30 min. The mixture is then homogenized in a three-dimensional powder mixer at 12 r / min for 26 h. After homogenization, the powder is removed and placed in a 90 mm diameter circular graphite mold. Two 90 mm diameter circular graphite papers are placed at the bottom, and the homogenized powder is slowly spread evenly in the mold. Two more 90 mm diameter circular graphite papers are placed on top. Under argon gas purging, the mixture is cold-pressed at 60 MPa for 10 min. The temperature is then increased to 200℃ at a rate of 20℃ / min, and the pressure is increased to 100 MPa for hot pressing for 5 h. Afterward, the pressure is released, and the mixture is heated to 1200℃ without pressure and held at that temperature for 4 hours. h; After the temperature drops to 600℃, it is cooled to room temperature by filling with inert gas. After removal, it is polished using a metallographic polishing machine to remove the graphite paper on the surface of the hot-pressed blank. During polishing, metallographic spray polishing agent is sprayed 5 times. After polishing, its weight m1 is weighed, which is 4531 g. The polished blank is placed in a high-temperature and high-pressure reactor containing 2 L of 250 g / L sodium hydroxide solution, heated to 250℃, and kept at this temperature for 4 h to dissolve. After dissolution, the nickel foam disperses into powder. Comparative Example 2

[0025] Prepare nickel powder with a purity of 99.99% and an average particle size of 10-20 μm; analytically pure spherical zinc oxide with a particle size of 0.5 mm; and corn starch with a particle size of 80 μm, weighing 500 g, 4500 g, and 75 g respectively. All are poured into a 2 L stainless steel container, and argon gas is introduced for 30 min. The mixture is then homogenized in a three-dimensional powder mixer at 12 r / min for 26 h. After homogenization, the powder is removed and placed in a 90 mm diameter circular graphite mold. Two 90 mm diameter circular graphite papers are placed at the bottom, and the homogenized powder is slowly spread evenly in the mold. Two more 90 mm diameter circular graphite papers are placed on top. Under argon gas purging, the mixture is cold-pressed at 60 MPa for 10 min. The temperature is then increased to 200℃ at a rate of 20℃ / min, and the pressure is increased to 100 MPa for hot pressing for 5 h. Afterward, the pressure is released, and the mixture is heated to 1200℃ without pressure and held at that temperature for 4 hours. h; After the temperature drops to 600℃, it is cooled to room temperature by filling with inert gas. After removal, it is polished using a metallographic polishing machine to remove the graphite paper on the surface of the hot-pressed blank. During polishing, metallographic spray polishing agent is sprayed 5 times. After polishing, its weight m1 is weighed, and the weight is 4536 g. The polished blank is placed in a high-temperature and high-pressure reactor containing 2 L of 250 g / L sodium hydroxide solution, heated to 250℃, and kept at this temperature for 4 h to dissolve. It was found that some nickel powder was dispersed in the solution. The blank was then transferred to a reactor containing 2 L of fresh pure water and boiled for 4 h. After removing the blank, it was rinsed 5 times with running water and vacuum dried at 80℃ for 10 h to obtain dry nickel foam. The blank weighs 256 g, but its mechanical properties are poor and it can be broken by hand. Comparative Example 3

[0026] Prepare nickel powder with a purity of 99.99% and an average particle size of 10-20 μm; analytically pure spherical zinc oxide with a particle size of 0.5 mm; and potato starch with a particle size of 80 μm, weighing 500 g, 4500 g, and 75 g respectively. All are poured into a 2 L stainless steel container, and argon gas is introduced for 30 min. The mixture is then homogenized in a three-dimensional powder mixer at 12 r / min for 26 h. After homogenization, the powder is removed and placed in a 90 mm diameter circular graphite mold. Two 90 mm diameter circular graphite papers are placed at the bottom, and the homogenized powder is slowly spread evenly in the mold. Two more 90 mm diameter circular graphite papers are placed on top. Under argon gas purging, the mixture is cold-pressed at 60 MPa for 10 min; then heated to 600℃ at a rate of 20℃ / min, and pressurized to 80 MPa for 5 h; finally, the pressure is released, and the mixture is heated to 1200℃ without pressure and held at that temperature for 4 hours. h; After the temperature drops to 600℃, it is cooled to room temperature by filling with inert gas. After removal, it is polished using a metallographic polishing machine to remove the graphite paper on the surface of the hot-pressed blank. During polishing, metallographic spray polishing agent is sprayed 5 times. After polishing, its weight m1 is weighed, and the weight is 4524 g. The polished blank is placed in a high-temperature and high-pressure reactor containing 2 L of 250 g / L sodium hydroxide solution, heated to 250℃, and kept at this temperature for 4 h to dissolve. It was found that some nickel powder was dispersed in the solution. The blank was then transferred to a reactor containing 2 L of fresh pure water and boiled for 4 h. After removing the blank, it was rinsed with running water 5 times and vacuum dried at 80℃ for 10 h to obtain dry nickel foam. The blank weighs 278 g, but its pore size is inconsistent and its shape is irregular, and it can be broken by hand.

[0027] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing nickel foam, characterized in that, Includes the following steps: S1) Nickel, zinc oxide, and potato starch are mixed and then subjected to cold pressing, low-temperature hot pressing, and sintering in sequence; the low-temperature hot pressing is performed at a pressure of 80~100 MPa, a temperature of 150~200℃, and a time of 3~5 h; the mass ratio of nickel, zinc oxide, and potato starch is 1:(8~9):(0.15~0.6). S2) The product obtained in step S1) is soaked in an alkaline solution to obtain nickel foam.

2. The preparation method according to claim 1, characterized in that, The porosity of the nickel foam is 80-86%.

3. The preparation method according to claim 1, characterized in that, In step S1), the particle size of the potato starch is 70~90 μm.

4. The preparation method according to claim 1, characterized in that, In step S1), the nickel element is nickel powder with an average particle size of 10~20 μm; The zinc oxide is spherical zinc oxide with a particle size of 0.3~0.6 mm.

5. The preparation method according to any one of claims 1 to 4, characterized in that, In step S1), the pressure of the cold pressing is 40~60 MPa, and the time is 5~10 min.

6. The preparation method according to any one of claims 1 to 4, characterized in that, In step S2), the sintering temperature is 1000~1200℃ and the time is 2~3 h.

7. The preparation method according to any one of claims 1 to 4, characterized in that, In step S3), the soaking is carried out at 200~250℃ for 2~4 hours.

8. The preparation method according to any one of claims 1 to 4, characterized in that, In step S3), the alkaline solution is selected from at least one of sodium hydroxide solution, potassium hydroxide solution and barium hydroxide solution.

9. The preparation method according to claim 8, characterized in that, In step S3), the concentration of the alkaline solution is 230~250 g / L.

Citation Information

Patent Citations

  • Preparation method of medical porous metal implant material

    CN102475904A

  • Foam metal nickel and preparation method thereof

    CN110732671A